2017
DOI: 10.2320/matertrans.m2017265
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Yttrium Addition on Plastic Deformation of Magnesium

Abstract: Tensile tests of single crystalline and polycrystalline Mg-Y alloys were carried out at room temperature to investigate the in uence of yttrium on activation of slip systems and to clarify the relationship between ductility of magnesium and the activation of slip systems. Tensile directions of single crystals and polycrystals were parallel to (0001) and their rolling direction, respectively. Mg-(0.6-1.1)at%Y alloy single crystals yielded due to the rst order pyramidal slip (FPCS). Yield stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…2 and 3, indentation morphology changed from elliptic to circular with increasing yttrium content, revealing the change in slip degree. Rikihisa et al 14) applied MgY alloy single crystals with different yttrium contents to tensile tests and reported that not only SPCS but also first order pyramidal ©c + aª slip (FPCS) were activated and that CRSS for FPCS increased by yttrium addition. Therefore, the difference between morphologies in 05Y and 09Y indentations would be caused by the difference in the activation of FPCS.…”
Section: A D V a N C E V I E Wmentioning
confidence: 99%
See 1 more Smart Citation
“…2 and 3, indentation morphology changed from elliptic to circular with increasing yttrium content, revealing the change in slip degree. Rikihisa et al 14) applied MgY alloy single crystals with different yttrium contents to tensile tests and reported that not only SPCS but also first order pyramidal ©c + aª slip (FPCS) were activated and that CRSS for FPCS increased by yttrium addition. Therefore, the difference between morphologies in 05Y and 09Y indentations would be caused by the difference in the activation of FPCS.…”
Section: A D V a N C E V I E Wmentioning
confidence: 99%
“…CRSSs for basal slip and second order pyramidal ©c + aª slip (SPCS) have been reported to change when aluminum, 911) zinc 12,13) and yttrium 13,14) are added to magnesium. Also, the loading direction to cause f10 12g twins, a typical deformation twin of HCP metals, is known to depend on c/a; the critical value is ffiffi ffi 3 p…”
Section: Introductionmentioning
confidence: 99%
“…Four, one, and three specimens were prepared for Mg0.54 at% Y (0.5Y), Mg0.9 at% Y (0.9Y), and Mg1.21 at% Y (1.2Y), respectively. Data of pure magnesium (Mg) and Mg0.9 at% Y alloy (0.9Y-2) 7) were used for comparison. 0.9Y-2 was also produced by casting, rolled and annealing.…”
Section: +1mentioning
confidence: 99%
“…0.9Y-2 was also produced by casting, rolled and annealing. 7) Specimens were mechanically polished using emery paper (# 400-4000), an MD-Nap (Struers), and diamond spray 1 mm (Struers). Specimen surfaces after mechanical polishing were chemically polished to mirror using a polishing cloth soaked in a solution (HNO 3 :H 2 O 2 :C 2 H 5 OH = 5:7:20).…”
Section: +1mentioning
confidence: 99%
See 1 more Smart Citation